Efektivitas Media ICT terhadap Hasil Belajar Akuntansi Instansi Pemerintah - Anindita Safira Arlina; Andi Kristanto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aimed to determine the effectiveness of ICT-based learning media, namely Canva, Doratoon, and Quizizz, on students’ learning outcomes in the Government Institution Accounting subject. The study was motivated by low student learning outcomes and the limited use of interactive ICT-based learning media in the learning process. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The population consisted of 106 students of Grade XI Accounting and Institutional Finance at SMK Negeri 1 Demak, with a sample of 70 students divided into experimental and control classes. Data collection techniques were conducted through pretest and posttest instruments. Data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The results showed that the experimental class experienced a higher increase in learning outcomes compared to the control class. Hypothesis testing obtained a significance value of 0.000 (<0.05), indicating a significant difference between the two classes. Therefore, the use of ICT-based learning media was proven effective in improving students’ learning outcomes in Government Institution Accounting learning.